2015
DOI: 10.1080/10538712.2015.1057667
|View full text |Cite
|
Sign up to set email alerts
|

The Dialectic of Chaos and Control in the Experience of Therapists Who Work With Sexually Abused Children

Abstract: The aim of this study is to contribute to the understanding the interaction between the emotionally destructive intensity of the trauma and forces that foster growth in therapists who treat sexually abused children. Data were collected through in-depth semistructured interviews with 14 experienced social workers. Content analysis reveals two emotional poles. At one pole, the dominant experiences are anxiety, turmoil, and intrusion that disrupted the order in the interviewee's secure world. At the opposing pole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Vicarious trauma is described as “the unique, negative, and accumulative changes that can occur to clinicians who engage in an empathetic relationship with clients” (McCann & Pearlman, 1990, p. 131). The development of vicarious trauma is directly related to client disclosures of trauma that are often detailed and graphic that occur during a therapeutic relationship (Possick, Waisbrod, & Buchbinder, 2015). Theoretical literature suggests that clinicians with a personal history of trauma may be more vulnerable to the impact of working with survivors of CSA than clinicians without such history (Pearlman & Saakvitne, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Vicarious trauma is described as “the unique, negative, and accumulative changes that can occur to clinicians who engage in an empathetic relationship with clients” (McCann & Pearlman, 1990, p. 131). The development of vicarious trauma is directly related to client disclosures of trauma that are often detailed and graphic that occur during a therapeutic relationship (Possick, Waisbrod, & Buchbinder, 2015). Theoretical literature suggests that clinicians with a personal history of trauma may be more vulnerable to the impact of working with survivors of CSA than clinicians without such history (Pearlman & Saakvitne, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…There is a real sense of these emotions being overwhelming (6, 9, 13), draining (8) and difficult to control (9, 16). Possick et al (2015) refer to the notion of emotional heaviness and resulting turmoil that therapists experience when engaging with trauma survivors. They proposed that identifying one's own vulnerabilities in a client can mean that a therapist's work becomes allconsumingintruding on and infiltrating their personal life.…”
Section: Emotional Experiencesmentioning
confidence: 99%
“…Many of the therapists reported that they experienced intrusive thoughts, images and nightmares about their client's trauma (1-4, 7, 9, 13-14, 16). Possick et al (2015) described how this imagery flooded, intruded and infiltrated the therapist's personal life. There is a sense of re-playing the trauma in one's own head as if it is in real time and not being able to get it out of one's head (2,9).…”
Section: Cognitive Experiencesmentioning
confidence: 99%
“…Overtime, practitioners engaging in empathic relationships hear numerous stories of human atrocity, creating a dark and unpleasant repertoire of client-disclosed trauma. Accordingly, practitioners experience a multifaceted process of adaption to cope with the disclosed traumatic material (Possick, Waisbrod, & Buchbinder, 2015).Cognitive changes can occur within the practitioner, creating intrusive imagery from client material, hyper vigilance in one's personal life, decreased sense of safety for self and loved ones, and an overall negative skew of the practitioner's worldview (Aparicio et al, 2013;Iqbal, 2015;Osofsky, Putman, & Lederman, 2008).…”
Section: What Is Vicarious Traumamentioning
confidence: 99%
“…Symptomology can be divided into four broad categories: (a) avoidant behaviors, such as escalated absenteeism from work, withdrawal from family members, social isolation from friends, and/or avoidance of sexual intimacy with partner(s); (b) arousal symptoms, displayed in hyper arousal for the safety of self and loved ones, increase in stress-induced medical conditions and illnesses, general fearfulness, and/or heightened suspicion of others; (c) changes in cognitive schemas, evidenced by engagement in dysfunctional coping skills, decrease in clinical service provision and general work ethic, intensified pessimistic worldview, apathy or negative change in spiritual beliefs; and (d) intrusive imagery through aversive daydreams, mental images, or nightmares (Aparicio et al, 2013;Barrington & Shakespeare-Finch, 2013;Branson et al, 2014;Ilesanm & Eboiyehi, 2012;Mairean & Turliuc, 2012;Mishori, Mujawar, & Ravi, 2014;Possick et al, 2015;Sansbury, Graves, & Scott, 2015;Vrklevski& Franklin, 2008;Wies& Coy, 2013).Research indicates that intrusive imagery is the most commonly endorsed symptom of vicarious trauma (Branson, 2011;Bride et al, 2004). Additional professional symptoms are increased cynicism and/or misplaced anger toward clients, decrease in quality service provision due to avoidance of client disclosures of trauma, poor ethical decision making, and ultimately, practitioners leaving the field altogether due to the rigors of the work (Iqbal, 2015;Pryce et al, 2007;Shepard, 2013).…”
Section: What Is Vicarious Traumamentioning
confidence: 99%